Calcified Leg Ulcers in Older Patients: Clinical Description, Morphology, and Chemical Characterization. Issue 1 (31st July 2021) - Colboc, Hester; Fontaine, Juliette; Bazin, Dominique; Frochot, Vincent; Letavernier, Emmanuel; Daudon, Michel; Laporte, Naomi; Rouzière, Stéphan; Reby, Michael; Galezowski, Agnes; Forasassi, Christine; Meaume, Sylvie
Abstract: Chronic wounds, including leg ulcers, constitute an important medical problem among older patients. Dystrophic calcifications (DC) are associated with a variety of disorders, including leg ulcers. The aim of this study was to report the clinical and biological characteristics of older patients with DC in leg ulcers and to determine the morphology and chemical composition of these calcifications. We conducted a prospective monocentric study in our Geriatric-Wound and Healing ward, Rothschild Hospital, Paris, from January 2018 to December 2019. Patients with leg ulcers were screened for DC by palpation. Patients' clinical, biological, and radiological findings were collected. DC morphology was analyzed using field-emission scanning electron microscopy and chemical composition was analyzed using µFourier transform infra-red spectroscopy and X-ray Fluorescence. Ten (7%) of the 143 patients hospitalized for leg ulcers presented DC. Older patients with DC were more likely to have leg ulcers with venous insufficiency ( p = .015), colonized by Pseudomonas aeruginosa (p = .026), with a longer healing evolution ( p = .0072) and hypercalcemia ( p = .041 ). Five DC were extracted from ulcers: 2 presented 500 nm lacunar spheres and intermingled fibrils of about 10 nm in diameter, consistent with bacterial and biofilm imprints. DC were always composed of calcium–phosphate apatite and associated to the presence of zinc. Our analyses were consistent with the involvement of microorganisms and inflammatory process in DC formation. Early management of venous insufficiency, treatment of chronic bacterial colonization and use of calcium-solubilizing drugs seem to be rational strategies for calcified leg ulcer management in older patients.